Walking boosts your performance in making additions and subtractions - Anelli, Filomena; Lugli, Luisa; Baroni, Giulia; Borghi, Anna M.; Nicoletti, Roberto (Frontiers in Psychology, 2014)
Previous research demonstrates that the processing of spatial information and numerical magnitude are strictly interwoven. Recent studies also provide converging evidence that number processing is influenced by body movements. In the present study we further investigate this issue by focusing on whether and how motions experienced with the whole body can influence arithmetical calculations. We asked participants to make additions or subtractions while experiencing leftward and rightward motions. Data revealed the emergence of a congruency effect between the orientation inferred by the type of arithmetical calculations and the type of motions experienced along an horizontal axis.